Penyuluhan Tanda Bahaya Kehamilan Untuk Meningkatkan Kewaspadaan Dan Keselamatan Ibu Hamil - Siti Badria Asikin; Tenny Tarnoto; Natalia Debi Subani; Nurhayati Nurhayati; Rezqiqah Aulia Rahmat; Cakrawati R (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The maternal mortality rate (MMR) remains a health indicator that requires significant attention, especially in areas with limited health facilities. One contributing factor to the high MMR is pregnant women's limited knowledge of pregnancy danger signs, often leading to delays in seeking medical help. This community service activity aims to improve pregnant women's knowledge of pregnancy danger signs through integrated counseling and education. The activity was conducted in Village X and involved 45 pregnant women. The methods used included classroom counseling, interactive discussions, demonstrations of danger signs, distribution of leaflets, and knowledge evaluation using pre- and post-tests. The results showed a significant increase in knowledge, with an average pre-test score of 56.2 increasing to 86.7 in the post-test. Ninety-one percent of participants stated that this activity was very beneficial and increased their awareness of pregnancy risks. In conclusion, counseling on pregnancy danger signs is effective in increasing the knowledge and awareness of pregnant women. This activity is recommended for routine implementation by health workers as an effort to prevent complications early and improve maternal safety.